The Correlation of The Degree of COPD on The Quality of The Patients' Life with COPD: HUBUNGA DERAJAT PPOK DENGAN KUALITAS HIDUP PASIEN PPOK 2020 - Bayu Krisna Aji; Yati Tursini; Yosep Rohyadi; Sansri Diah KD (Jurnal Kesehatan Siliwangi, 2020)
ABSTRACT This research is motivated by the average incidence of COPD in West Java that exceeds the average in Indonesia and is one of the non-communicable diseases which is the main cause of death by golabal (Riskesdas, 2013). Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease characterized by obstruction of air flow and is progressive, so it is necessary to do efforts to improve nursing care because it will affect the quality of life of patients. This study aims to determine the relationship of COPD degrees with the quality of life of COPD patients. The research method used is systematic literature review or often abbreviated as SLR. The results of the synthesis of previous research data that have similar substance / theme have the result that the respondents are mostly elderly with age 50 years and over, male sex, and have a history of smoking, distribution of COPD degrees and distribution of the quality of life of COPD patients vary in each house ill data that can be concluded from the SLR results are patients with moderate COPD degrees, most of whom experience a good quality of life, and patients who have severe COPD degrees have poor quality of life. The conclusion of this study is that there is a relationship between the degree of COPD and the quality of life of COPD patients. It is recommended to other researchers to have a variety of research methods to prevent unwanted situations in working on research to be studied and to optimize the time and conditions for conducting research. Key words: Quality of life, COPD degrees